Effect of Different Growing Niches on Stand Structure of Highland Bamboo (Yushania alpina) in West Amhara, Northern Ethiopia - Amsalu Alamerew; Menale Mulu; Asmamaw Abtew; Demel Fanta; Beyene Alem; Melkamu Mekonnen; Mulugeta Asres (International Journal of Forestry Research)
The study was conducted to investigate the effects of different growing niches on the stand structure of highland bamboo (Yushania alpina) in west Amhara national regional state, northern Ethiopia. Four districts were selected purposively based on the existence of bamboo in different agroforestry practices. Inventory was carried out from 324 randomly selected plots of bamboo stands. The height of bamboo culms ranged between 12.2 ± 0.14 and 14.7 ± 0.12 m, and the diameter was between 4.9 ± 0.12 and 6.1 ± 0.11 cm with a mean value of 5.7 ± 0.102 cm. Growth performance (diameter and height size) based population distribution (histogram visualization) of bamboo stand indicated the normal distribution of height and diameter of culms. Density of culm varies between 19,188 ± 336 and 23,129 ± 390 culms ha−1 with an age composition of 26 : 45 : 29 ratio with 1 and 3 age classes. Diameters of the bamboo culms have inverse relationship with the age of bamboo culm. Clump stocking of highland bamboo varies between 953 ± 40 and 1220 ± 48 clump ha−1 with a culm : clump ratio of 1 : 47 ± 5 and 1 : 82 ± 6. Information on the stand structure of bamboo culms across niches is important to identify the productive plantation niche and develop a management plan for sustainable management and utilization of the bamboo resource.